Indentation Methods for Characterising the Mechanical and Fracture Behaviour of Polymer Nanocomposites - Lach, Ralf; Kim, Gyeong-Man; Adhikari, Rameshwar; Michler, Goerg H; Grellmann, Wolfgang (Nepal Journal of Science and Technology, 2013)
Morphological analysis of nanocomposites of polyethylene glycol (PEG) based polyurethanes (TPU) and polyhedral oligomeric silsesquioxanes (POSS) were performed using different techniques (transmission electron microscopy, small and wide X-ray scattering, differential scanning calorimetry) as a function of molecular weight of PEG and the PEG/POSS mole ratio. A strong interdependence in crystallisation behaviour between the two crystals species, i.e. the POSS nanocrystals about 5 nm in size and the crystals in the semicrystalline soft phase of TPU, were found. The mechanical properties (Vickers hardness under load and elastic modulus) determined using recording microindentation techniques at room temperature were significantly improved by POSS for two material formulations. Based on the results of polymethylmethacrylate (PMMA)/silica (SiO2) nanocomposites containing up to 20 wt.-% well-dispersed spherical silica nanoparticles, it has been shown that the indentation fracture mechanics is a straightforward, costand time-effective, powerful tool to analyse the fracture resistance for the novel polymer materials, such as brittle nanostructured polymer-ceramic hybrids. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 115-122 DOI: http://dx.doi.org/10.3126/njst.v13i2.7723